Phase I Clinical Trial Results of Auranofin, a Novel Antiparasitic Agent - Capparelli, Edmund V.; Bricker-Ford, Robin; Rogers, M. John; McKerrow, James H.; Reed, Sharon L. (Antimicrobial agents and chemotherapy, 2017)
Under an NIH priority to identify new drugs to treat class B parasitic agents, we performed high-throughput screens, which identified the activity of auranofin (Ridaura) against Entamoeba histolytica and Giardia intestinalis , major causes of water- and foodborne outbreaks. Auranofin, an orally administered, gold (Au)-containing compound that was approved by the FDA in 1985 for treatment of rheumatoid arthritis, was effective in vitro and in vivo against E. histolytica and both metronidazole-sensitive and -resistant strains of Giardia . We now report the results of an NIH-sponsored phase I trial to characterize the pharmacokinetics (PK) and safety of auranofin in healthy volunteers using modern techniques to measure gold levels. Subjects received orally 6 mg (p.o.) of auranofin daily, the recommended dose for rheumatoid arthritis, for 7 days and were followed for 126 days. Treatment-associated adverse events were reported by 47% of the subjects, but all were mild and resolved without treatment. The mean gold maximum concentration in plasma ( C max ) at day 7 was 0.312 μg/ml and the half-life ( t 1/2 ) 35 days, so steady-state blood levels would not be reached in short-term therapy. The highest concentration of gold, 13 μM (auranofin equivalent), or more than 25× the 50% inhibitory concentration (IC 50 ) for E. histolytica and 4× that for Giardia , was in feces at 7 days. Modeling of higher doses (9 and 21 mg/day) was performed for systemic parasitic infections, and plasma gold levels of 0.4 to 1.0 μg/ml were reached after 14 days of treatment at 21 mg/day. This phase I trial supports the idea of the safety of auranofin and provides important PK data to support its potential use as a broad-spectrum antiparasitic drug. (This study has been registered at ClinicalTrials.gov under identifier NCT02089048.)